2012
DOI: 10.1002/ajmg.a.35353
|View full text |Cite
|
Sign up to set email alerts
|

Variability in expression of a familial 2.79 Mb microdeletion in chromosome14q22.1–22.2

Abstract: Deletions in chromosome 14q22-23 have been associated with variable manifestations including malformations of the eye, limbs, palate, and brain, and with developmental and growth delay. Haploinsufficiency of BMP4, OTX2 and possibly SIX6 are thought to contribute to the phenotype. We present a three generation family with four individuals carrying a 2.79 Mb microdeletion 14q22.1-22.2 encompassing BMP4 but not OTX2 nor SIX6. The highly variable manifestations in this family range from multiple congenital malform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 26 publications
2
21
0
Order By: Relevance
“…Here, we identify two evolutionarily conserved regions 5′, and one 3′, of the six6 coding region, which independently control the late and early expression of six6 , respectively. We find the early enhancer is not only sufficient for eye field and optic vesicle expression of six6 , but also required for normal optic vesicle size, which is consistent with the established role for Six6 in regulating eye size, not only in animal models but also human patients (Aldahmesh et al, 2013; Bar-Yosef et al, 2004; Bennett et al, 1991; Cheng et al, 2015; Dixit et al, 2014; Fish et al, 2014; Fuhrmann et al, 2000; Lee et al, 2012; Lumaka et al, 2012; Nojima et al, 2010; Toy et al, 1998; Yariz et al, 2015; Zuber et al, 1999). The identification of distinct regions that function modularly, to independently control eye field/optic vesicle versus optic cup/mature retinal expression of six6 is consistent with the observation that some patients with SIX6 mutations present with anophthalmia or microphthalmia, while others have normal size eyes, yet develop primary open angle glaucoma (POAG).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Here, we identify two evolutionarily conserved regions 5′, and one 3′, of the six6 coding region, which independently control the late and early expression of six6 , respectively. We find the early enhancer is not only sufficient for eye field and optic vesicle expression of six6 , but also required for normal optic vesicle size, which is consistent with the established role for Six6 in regulating eye size, not only in animal models but also human patients (Aldahmesh et al, 2013; Bar-Yosef et al, 2004; Bennett et al, 1991; Cheng et al, 2015; Dixit et al, 2014; Fish et al, 2014; Fuhrmann et al, 2000; Lee et al, 2012; Lumaka et al, 2012; Nojima et al, 2010; Toy et al, 1998; Yariz et al, 2015; Zuber et al, 1999). The identification of distinct regions that function modularly, to independently control eye field/optic vesicle versus optic cup/mature retinal expression of six6 is consistent with the observation that some patients with SIX6 mutations present with anophthalmia or microphthalmia, while others have normal size eyes, yet develop primary open angle glaucoma (POAG).…”
Section: Discussionsupporting
confidence: 86%
“…Six6 is expressed in the retina through all stages of eye development and its mutation results in diseases as distinct as anophthalmia and primary open angle glaucoma (Aijaz et al, 2005; Aldahmesh et al, 2013; Cheng et al, 2015; Elliott et al, 1993; Gallardo et al, 1999; Gallardo et al, 2004; Huai et al, 2011; Lemyre et al, 1998; Lumaka et al, 2012; López-Ríos et al, 1999; Nolen et al, 2006; Suda et al, 1999; Toy et al, 1998; Toy and Sundin, 1999; Yariz et al, 2015; Zuber et al, 1999) and reviewed in (Abu-Amero et al, 2015). How Six6 expression is controlled in the optic cup and mature retina has been extensively investigated in multiple species (Conte and Bovolenta, 2007; Larder et al, 2011; Tomarev, 1999; Viczian et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In 1991, Bennett et al was the first to suggest a relationship between the 14q22–q23 deletion and the presence of anophthalmia/microphthalmia (A/M) and pituitary malformations. This observation was followed by at least nine more reports of patients with A/M and other eye defects, and deletions of the 14q22–q23 region [Elliott et al, ; Lemyre et al, ; Nolen et al, ; Thienpont et al, ; Bakrania et al, ; Hayashi et al, ; Reis et al, ; Lumaka et al, ; Pearce et al, ]. These included an article that described four family members with the same deletion of 14q22.1–q22.2 and highly variable manifestations [Lumaka et al, ]; therefore, we present the second reported family carrying the same chromosomal deletion, and the first with a clinical diagnosis of a syndrome [Frías et al, ; Martínez‐Frías et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Anophthalmia and other ocular anomalies were associated with heterozygous defects in OTX2 [3,8,9] or BMP4 [7,10,11], and also with deletions involving both these genes [4,6,12]. While OTX2 was deleted in all our patients, BMP4 was deleted only in Patient 1 (Figure 2).…”
Section: Discussionmentioning
confidence: 80%